Movement and Home Range of the Translocated Komodo Dragons (Varanus komodoensis Ouwens, 1912) in Flores, East Nusa Tenggara, Indonesia - Ramadhan, Tubagus Muhamad Daffa; Kusrini, Mirza Dikari; Aini, Yusratul; Mahmud, Arief (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
One of the conservation efforts for the Komodo Dragon (Varanus komodoensis) is the translocation of the Komodo. Six juvenile captive-bred Komodo Dragons were translocated from Bogor to Wae Wuul Nature Reserve, East Nusa Tenggara Province, on 23rd September 2023. This research aims to calculate and describe home ranges total daily movements and the habitat conditions of Komodo Dragons. The research was carried out at the Wae Wuul Nature Reserve using the radio tracking method for 11 days, as most of the translocated Komodo Dragons could only survive in the short term. Results showed that translocated Komodo Dragons tend to stay near the initial release location. The average total daily movement translocated Komodo Dragons was 424.53 m day–1 with an average home range of 34.11 ha and an average core area of 8.20 ha. The habitats used by Komodo Dragons are savanna and monsoon forests dominated by bushes and trees. The presence of feral dogs and vehicle road access have the potential to pose a threat to the translocated Komodo Dragons.